Endogeneity in the relation between poverty, wealth and life satisfaction - André Hajek (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This publication concentrates on the complex interplay between poverty, wealth and life satisfaction. Main areas of life are quantified in a multidimensional approach of poverty and wealth: Individual income, current health, occupational autonomy or employment status and also the mentioned life satisfaction. Data used in this publication were made available by the German Socio Economic Panel Study (SOEP) at the German Institute for Economic Research (DIW Berlin), Berlin. A period from 1998-2009 is examined. This study has two main goals: (1) To contribute to the interconnection between poverty, wealth and life satisfaction. (2) Besides, the endogeneity research regarding life satisfaction should be expanded. Reduced form vector-autoregressions (with first differences) were used to answer the questions. Therefore, granger-causality can be supposed. Major findings: An initial rise in life satisfaction can improve income and health, but not job autonomy. However, even the probability of returning from unemployment to employment can increase. Gender-specific differences are discussed. – – Der Fokus dieser Arbeit liegt auf der komplexen Wechselwirkung zwischen Armut, Reichtum und Lebenszufriedenheit. Die Konzentration gilt zentralen Bereichen des Lebens: Individuelles Einkommen, subjektiver Gesundheitszustand, berufliche Autonomie bzw. Erwerbstätigkeit sowie der angesprochenen Lebenszufriedenheit. Die Daten dieser Publikation beruhen auf Zahlen des Soziooekonomischen Panels (SOEP) am Deutschen Institut für Wirtschaftsforschung (DIW Berlin), Berlin. Es wird ein Zeitraum von 1998-2009 betrachtet. Dadurch wird überwiegend ein Beitrag zur Endogenitätsfrage geleistet und das verzweigte Zusammenspiel dieser Größen abgebildet. Methodisch wird dazu auf Reduced Form Vektorautoregressionen (mit First Differences) zurückgegriffen. Granger-Kausalität kann angenommen werden. Zentrale Ergebnisse: Ein anfänglicher Anstieg der Zufriedenheit erhöht das individuelle Einkommen sowie den Gesundheitszustand, aber nicht die berufliche Autonomie. Hingegen kann sich die Wahrscheinlichkeit erhöhen, dass man von einer Arbeitslosigkeit zurück in die Vollerwerbstätigkeit gelangt. Diskrepanzen zwischen den Geschlechtern werden diskutiert.
Keywords: I19; I31; I32; J64; 330; Lebenszufriedenheit; Arbeitslosigkeit; SOEP; Vector-Autoregressionen; Endogenität; Einkommen; Gesundheit; berufliche Autonomie; life satisfaction; unemployment; SOEP; vector autoregressions; endogeneity; income; health; occupational autonomy